Analisis Kebijakan Pengelolaan Rumah Susun di Kota Semarang - Billy Yordan; Yuwanto .; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
AbstractThis study was conducted to explain the process of management of flats in the city of Semarang and to know the obstacles that occur in the process of managing these flats. Flats is one good program to be implemented in urban areas such as the city of Semarang. Which is the main target for the victims of natural disasters, and low-income people who do not have homes .The subjects of this study is City Planning and housing and as a manager UPTD Home Rent Flats. The method used is qualitative research methods. Researchers collected data through interviews and observation in flats and look for supporting data.From the results of research conducted in the shade DTKP UPTD Rental Homes . It can be seen that the process of managing flats starting with the opening of registration for the MBR renting flats that do not have homes , people do miss every 1 week 2 times / more , with the balance of the income factor . MBR occupying flats to rent between Rp.55.000 pay up to Rp . 110,000 per month and is based on the Decree of the Head DTKP . However, in relation to the implementation of the maintenance carried out by housing and settlement . In the system of payment of rent , there are two systems that are currently running. First , the staff UPTD came to visit residents in public housing , and Second people can immediately pay directly to the manager 's office . There are barriers that result in less than optimal management , among others , took to the field staff which is inadequate because less people and factors affecting age , weak regulatory system , triggering residents to sign and peddle copies of flats , unpredictable weather conditions and the overlap overlapping interests in the management of flats.To reduce such violations shall have full authority managers, personnel managers should be added and placed in each location flats , the need to cooperate with other agencies in order to maintain a sense of comfort for the citizens of towers , the manager should also have an attitude of firmness to prevent deviations often occur .keywords : process management , residential , flats